Real-Life Analysis of Therapeutic Management and Its Correlation With the Dermatology Life Quality Index Score in 108 Patients With Pustular Psoriasis: An Italian Monocenter Study - Dario Buononato; Emanuele Scala; Pierfrancesco Benvenuto; Stefano Caccavale; Eugenia Veronica Di Brizzi; Roberta Di Caprio; Giuseppe Argenziano; Anna Balato (Dermatology Practical & Conceptual)
Introduction: Pustular psoriasis (PP) is a rare life-threatening skin disease with negatively impact on quality of life (QoL). Clinically, it may be systemic (generalized pustular psoriasis [GPP]) or localized on palms and soles (palmoplantar pustulosis [PPP]). It is not rare to observe plaque psoriasis associated with GPP.